The Usage Of Counterfeit Materials In Grey Structures In Peshawar Construction Industryy - Sheeraz, Muhammad; Ahad, Muhammad Zeeshan (Advances in Social Sciences Research Journal, 2017)
The construction industry can be categorized as one of the most important Industries in modern society. Unfortunately, these days, the construction industry has been affected by a menace of counterfeiting. Author has found that counterfeiting has become a significant and growing problem within the construction industry. In order to analyze the impact and effects of counterfeit materials and their usage in the construction oriented industry of Peshawar (KP).The opinion of 96 respondents of the Peshawar construction industry (client, contractor and consultants)were analyzed. From the study it was observed that the problem of counterfeiting was increasing where the factor was ranked 1st through the Relative importance index and the least was observed as counterfeit products/goods are durable and reliable in the construction industry. To maintain an updated approved vendor list, verify as high in the supply chain as possible.